2021
DOI: 10.1111/1346-8138.15843
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab shows slow, steady effectiveness for intractable prurigo in patients with atopic dermatitis

Abstract: Prurigo lesions in atopic dermatitis are intractable. This single-center, retrospective study examined dupilumab's clinical effects on intractable prurigo. Twenty adult atopic dermatitis patients (12 with prurigo, eight without) were administrated dupilumab. Its effects on itching and disease severity were examined with Numerical Rating Scale-Itch (NRS-I), Eczema Area and Severity Index (EASI), and Investigator Global Assessment (IGA) scores; body surface areas (BSA); and thymus-and activation-regulated chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Th2 responses, such as IL‐13 and IL‐4R, which were highly expressed in APN, suggest that the novel biologics for AD, dupilumab/tralokinumab/lebrikizumab, may be equally effective in the treatment of prurigo. The latest series of clinical trials confirmed this hypothesis, 20–23 but the onset time of dupilumab in the treatment of APN is often longer than that of AD, 4,12 suggesting the presence of other potential mechanisms underlying the pathogenesis of the former. Tsoi et al reported that IL‐31 plays a critical upstream role in the pathogenesis of PN 8 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Th2 responses, such as IL‐13 and IL‐4R, which were highly expressed in APN, suggest that the novel biologics for AD, dupilumab/tralokinumab/lebrikizumab, may be equally effective in the treatment of prurigo. The latest series of clinical trials confirmed this hypothesis, 20–23 but the onset time of dupilumab in the treatment of APN is often longer than that of AD, 4,12 suggesting the presence of other potential mechanisms underlying the pathogenesis of the former. Tsoi et al reported that IL‐31 plays a critical upstream role in the pathogenesis of PN 8 .…”
Section: Discussionmentioning
confidence: 96%
“…Prurigo nodularis (PN) is a chronic skin disease characterized by intensely pruritic nodular lesions 1,2 . It has greater itch intensity and causes poorer quality of life than other common skin disorders 2–4 . Traditional therapies such as antihistamines, glucocorticoids and phototherapy are largely ineffective for PN 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present report confirmed this trend with a greater number of patients. Likewise, other real‐world studies in Japanese patients with AD have also shown marked and rapid improvement in skin eruptions and erythema, as well as in TARC and LDH serum levels at 1 month, while there was a gradual improvement in prurigo nodules and serum total IgE level 30–33 …”
Section: Discussionmentioning
confidence: 80%
“…3 Existing clinical trials have only assessed response until 24 weeks, with long-term impact of therapy (including rates of secondary treatment failure) remaining unclear. 3 , 4 , 5 …”
mentioning
confidence: 99%